Modelling of Dam-Weir Operations for Environmental Quality - Mah, D.Y.S.; Putuhena, F.J. (Universiti Malaysia Sarawak, (UNIMAS), 2014)
It is the desire of many societies to have clean and safe potable water sources. As manmade structures are built in water supply catchments for the purposes to increase safe yield, then facilities management of these structures should be steered towards environmental quality. Hydraulics over a weir is well studied. However, this paper probes into benchmarking of flows over a Batu Kitang Weir to guide operations of an upstream Bengoh Dam in Sarawak, Malaysia. Flow releases from the dam are tried and routed through Sarawak Kiri River to achieve supercritical states at weir by means of computer modelling. For daily dam-weir operations, the modelling results suggest a condition of 20 m3/s < dam releases < 200 m3/s to meet raw water demand as well as adequate river flow regulation.